A biomaterial-based therapy using a sodium hyaluronate/bioglass composite hydrogel for the treatment of oral submucous fibrosis. (February 2023) - Guo, Zhen-Xing; Zhang, Zhaowenbin; Yan, Jian-Fei; Xu, Hao-Qing; Wang, Shu-Yan; Ye, Tao; Han, Xiao-Xiao; Wang, Wan-Rong; Wang, Yue; Gao, Jia-Lu; Niu, Li-Na; Chang, Jiang; et al.
Abstract: Oral submucous fibrosis (OSF) is a chronic, inflammatory and potentially malignant oral disorder. Its pathophysiology is extremely complex, including excessive collagen deposition, massive inflammatory infiltration, and capillary atrophy. However, the existing clinical treatment methods do not fully take into account all the pathophysiological processes of OSF, so they are generally low effective and have many side effects. In the present study, we developed an injectable sodium hyaluronate/45S5 bioglass composite hydrogel (BG/HA), which significantly relieved mucosal pallor and restricted mouth opening in OSF rats without any obvious side effects. The core mechanism of BG/HA in the treatment of OSF is the release of biologically active silicate ions, which inhibit collagen deposition and inflammation, and promote angiogenesis and epithelial regeneration. Most interestingly, silicate ions can overall regulate the physiological environment of OSF by down-regulating α-smooth muscle actin (α-SMA) and CD68 and up-regulating CD31 expression, as well as regulating the expression of pro-fibrotic factors [transforming growth factor-β1 ( TGF-β1 ), interleukin-10 ( IL-10 ), tumor necrosis factor-α ( TNF-α ) and tissue inhibitors of metalloproteinase-1 ( TIMP-1 )] and anti-fibrotic factors [interleukin-1β ( IL-1β )] in macrophage. In conclusion, our study shows that BG/HA has great potential in the clinical treatment of OSF, which provides an important theoretical basis for the subsequent development of new anti-fibrotic clinical preparations. Statement of significance: : Oral submucous fibrosis (OSF) is a chronic, inflammatory and potentially malignant mucosal disease with significant impact on the quality of patients' life. However, the existing clinical treatments have limited efficacy and many side effects. There is an urgent need for development of specific drugs for OSF treatment. In the present study, bioglass (BG) composited with sodium hyaluronate solution (HA) was used to treat OSF in an arecoline-induced rat model. BG/HA can significantly inhibit collagen deposition, regulate inflammatory response, promote angiogenesis and repair damaged mucosal epithelial cells, and thereby mitigate the development of fibrosis in vivo . Gaphical abstract: Image, graphical abstract